PENERAPAN MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN GEOGRAFI KELAS XI SMAN 5 PONTIANAK - Oraza, Ozha; Parijo, Parijo; Sugiarto, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis study aims to determine the effect of the application Problem Based Learning to student learning outcomes in the biosphere material class XI IIS Senior High School 5 Pontianak. The study method used is an experimental in the form of a Quasi Experiment Design and a Nonequevalent Control Group Design. The population of this study was all students of class XI IIS, amounting to 144 student. The sampling was students of class XI IPS 4, totaling 31 students as an experimental class and 32 students in the class XI IIS 3 as the control class. Data collection techniques using measurement techniques and data collection tools are objective written test in the form of multiple choice. The results obtained with an average of 64.21 control class final tests and an average of 74.24 experimental class final tests. T-test results obtained tcount of 3.56 and ttable (? = 5% with dk = 61) of 1.6707, which means tcount (3.56)> ttable (1.6707), Ha is accepted. So, it was concluded that there were differences in the average student learning outcomes between the application of the problem based learning model and the application of conventional methods in learning geography class XI IIS Senior High School 5 Pontianak.Keyword : Learning Geography, Learning Outcomes, Problem Based Learning